Angpt2 Induces Mesangial Cell Apoptosis through the MicroRNA-33-5p-SOCS5 Loop in Diabetic Nephropathy - Yi-Chun Tsai; Po-Lin Kuo; Wei-Wen Hung; Ling-Yu Wu; Ping-Hsun Wu; Wei-An Chang; Mei-Chuan Kuo; Ya-Ling Hsu (Elsevier, 2018)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease. Mesangial cell (MC) loss is correlated with worsening renal function in DN. Disturbance of angiopoietin (Angpt)/Tie ligand-receptor system causes inflammation and abnormal angiogenesis. This association between elevated circulating Angpt2 and poor renal outcome has been in DN patients. However, the pathogenic role of Angpt2 in the MCs remains unknown. We found serum Angpt2 levels were elevated in type 2 diabetes mellitus (DM) patients and db/db mice, which correlated with albuminuria. Angpt2 synergistically induced MC apoptosis under high glucose (HG), and miR-33-5p regulated Angpt2-inducing MC apoptosis treated with HG. Loss of miR-33-5p increased suppressor of cytokine signaling 5 (SOCS5), leading to the inhibition of Janus kinase 1 and signal transducer and activator of transcription 3 signaling transduction. Elevated expression of SOCS5 was found in the MCs in kidney sections of both db/db mice and type 2 DM patients. Decreased miR-33-5p levels were found in the urine of db/db mice and type 2 DM patients, and miR-33-55p levels negatively correlated with albuminuria. Angpt2 leads to MC apoptosis via the miR-33-5p-SOCS5 loop in DN. miR-33-5p is predictive of kidney injury in DN. These findings may provide future applications in predicting renal dysfunction and the therapeutic potential of DN. Keywords: angiopoietin-2, miR-33, SOCS5, diabetic nephropathy, mesangial cell